Enterprise evolution, survival and the businesstype : from research to practice - Abatecola, Gianpaolo (Routledge focus on business and management., 2025)
The strategic journey taken by firms starts with entrepreneurial inception and can go all the way through adaptation to sustainable enterprise, exit, or failure. This book charts how new ventures grow through co-evolution and adaptation to get past the initial problems of being new, connecting theories of strategic management and entrepreneurship.Conceptually, the author paints an integrated picture of the challenges arising from the enterprise life cycle. Based on research, the book is also accessible to practitioners and students, in that it provides practice-oriented takeaways about how enterprises can evolve and thrive in turbulent times.Together with executives, entrepreneurs, and policymakers, the book is intended for scholars and postgraduate students, interested in understanding strategic management and entrepreneurship from an evolutionary perspective.